The Romanticism of Political Science - Jokubaitis, Alvydas (Problemos, 2019)
The aim of the article is to demonstrate the relationship between modern political science and Romanticism. This is done by using Carl Schmitt’s conception of political romanticism and proposing some corrections to it. Schmitt failed to notice important similarities between the scientific concept of causa and the romantic concept of occasio. Modern political science is based on the same assumptions as the modern art of the romantic tradition. The researches of political science are conditioned by an unpolitical relationship with reality.
Keywords: political science; Romanticism; Carl Schmitt; Immanuel Kant